Optimal Transparency and Policy Intervention with Heterogeneous Signals and Information Stickiness - Jonathan James (The Manchester School, 2016)
A model economy subject to an aggregate demand disturbance and consisting of firms which are heterogeneously informed about that disturbance is considered, in order to investigate the policy implications of a monetary policymaker disclosing to firms collectively its own imperfect information about the state of aggregate demand. In the spirit of 'sticky information' models, not all firms respond promptly to the latest available information when making pricing decisions. With the policymaker able to adjust a monetary instrument to combat the aggregate demand shock, it is found that it cannot ever be optimal for the policymaker to disclose fully its own information. The paper proceeds to identify the circumstances which imply partial disclosure of this information would be optimal.